Indonemoura annamensis—a new species of stonefly from Vietnam (Plecoptera: Nemouridae) - Fochetti, Romolo; Ceci, Massimo (Zootaxa, 2016)
The amphinemurine genus Indonemoura Baumann (1975) was proposed for species previously included in the genera Protonemura Kempny and Nemoura Latreille. Baumann (1975) designated P. indica Kimmins, 1947 (in Kimmins 1946) as the type species. He also transferred 14 additional species from Protonemura and Nemoura into this genus. The genus is distributed mainly in the Oriental region (only one species from Tibet, close to the eastern border of the Palaearctic Region) and many new species have been added in the last decades (Zwick & Sivec 1980; Shimizu 1994a & b; Zhu et al. 2002; Li et al. 2005; Li & Yang 2005, 2006; Wang et al. 2006; Sivec & Stark 2010) including presently 53 species (DeWalt et al. 2009). Sivec & Stark (2010) first described three Indonemoura species from Vietnam, I. angulata, I. clavata, and I. tricantha. These three species are the only Indonemoura presently known for Vietnam.